2022
DOI: 10.1037/pspp0000423
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the complex relationship between work transitions and self-esteem and life satisfaction.

Abstract: Transitions in and out of work are common experiences with major repercussions for people’s lives. The complex link between work transitions and psychological adjustment is not well understood, however. In this preregistered study, we analyzed 11 waves of longitudinal data from a representative sample of 13,671 Dutch participants to examine the transactional effects between repeated work transitions (employment and unemployment) and psychological adjustment (self-esteem and life satisfaction). We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 133 publications
0
36
2
Order By: Relevance
“…College students face unique challenges as they transition from high school to college, so they are of particular interest [ 36 ]. College students are frequently subjected to increased accountability, competition, academic pressure, and time management requirements [ 38 , 40 ]. This change may result in decreased physical activity (PA), increased emotional and psychological stress, and sleep problems [ 30 , 36 ], as well as the onset of potentially harmful health behaviors such as drug and alcohol abuse [ 41 ], which could have a negative impact on learning experience and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…College students face unique challenges as they transition from high school to college, so they are of particular interest [ 36 ]. College students are frequently subjected to increased accountability, competition, academic pressure, and time management requirements [ 38 , 40 ]. This change may result in decreased physical activity (PA), increased emotional and psychological stress, and sleep problems [ 30 , 36 ], as well as the onset of potentially harmful health behaviors such as drug and alcohol abuse [ 41 ], which could have a negative impact on learning experience and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there is a dearth of data on the mental (quality of life and learning experience) and physical (physical self-esteem) outcomes associated with different PA levels among young adults and college students. There is a special interest in the college population because of the unique challenges that this cohort of young adults faces as they make the transition from high school to college [ 36 , 37 ], encountering greater accountability, competition, academic pressure, and time management demands [ 38 , 39 , 40 ]. Decreased physical activity (PA), expanded emotional and psychological stress, and sleep problems are all possible side effects of this change [ 30 , 36 ], as well as the onset of risky health behaviors such as drug and alcohol abuse [ 41 ], which may have an adverse effect on learning experience and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research suggests that global self-esteem has benefits for many life outcomes (Orth & Robins, 2022), but if global self-esteem influences domain-specific self-esteem, it is possible that changes in domain-specific self-esteem account for (i.e., mediate) some of the positive effects of global self-esteem. Third, if domain-specific self-esteem influences global self-esteem, this knowledge could help to better understand how global self-esteem is influenced by people’s experiences in important life domains, such as social relationships, school, and work (Filosa et al, 2022; Harris & Orth, 2020; Krauss & Orth, 2021; Reitz et al, 2022; Wagner et al, 2018). Thus, it is possible that domain-specific self-esteem mediates some of the effects of life experiences on global self-esteem.…”
Section: Theoretical Perspectives On the Relation Between Global And ...mentioning
confidence: 99%
“…Individual differences in self-esteem development indicate the degree to which self-esteem change deviates from the normative trajectory. Studies identified unique patterns of self-esteem development across the entire lifespan, including adolescence (Birkeland et al, 2012;Block & Robins, 1993), young adulthood (Chung et al, 2014;Hutteman et al, 2014), middle adulthood (Reitz, Luhmann, et al, 2022), and later adulthood (Shaw et al, 2010;Wagner, Gerstorf, et al, 2013). Some of these studies reported that a considerable number of people changed even in the opposite direction of the average trend.…”
Section: Individual Differences In Self-esteem Developmentmentioning
confidence: 99%